Technological interventions to enhance productivity and income in Arid Zones: A compilation of successful cases under the Farmer FIRST Programme - N A, Vijay Avinashilingam; Jat, N K; Meghwal, P R; Singh, Bhagwan; Singh, S K; Ram, Sharvan; Mola, C (Indian Farming, 2021)
Agriculture in arid western Rajasthan is very challenging due to low, erratic rainfall and limitedirrigation facilities. Under the prevailing climatic conditions, farmers are practising subsistencefarming with low farm income and profitability. As a consequence, distress land sale, diversion ofland for mining, urban migration, etc. are the common phenomenon observed in rural areas.Present article was formulated to document the successful technological interventions in terms ofvarietal intervention, inter cropping, crop diversification, nutrient management and productionof critical farm inputs coupled with capacity building and awareness generation practiced amongthe farming community in arid region to make farming more profitable and reduce livelihoodrisk. Most of the technological interventions were conducted through participatory mode in selectedlocale under ICAR - Farmer FIRST programme. The successful performances of narratedtechnologies at farmers’ field revealed that the technological interventions coupled with technicalbackstopping could definitely enhance the income of farmers and ensure livelihood security in aridregion in general and Jodhpur in particular.